44 Standardised enteral feeding protocols improve growth and clinical outcomes for infants on CICU. (23rd February 2023) - Kidd, Catherine; Hamzeh, Ramzi; Hoskote, Aparna; Rodrigues, Warren; O'Connor, Graeme
Abstract : Background: To determine effects of standardising feeding on; necrotising enterocolitis (NEC), parenteral nutrition (PN) duration, growth and length of stay (LOS) for infants on CICU. Methods: A single-centre retrospective chart review in infants admitted to CICU in November/December 2020 (pre-protocol) and May/June 2021 (post-protocol). A dietitian-led clinical team used diagnoses and clinical observations to determine whether infants should be nil by mouth, follow 'high-risk' or 'standard-risk' protocols. The 'standard-risk' protocol advised four hours of feeding at 30ml/kg/day, followed by increasing feeds to fluid allowance. 'High-risk' protocol infants advanced feeds by 15ml/kg/day (previously 0.5ml/kg/hour four hourly). An optional 'side-step' from 'high-risk' to 'standard-risk' was introduced following day three for stable infants. Donor expressed breast milk (EBM) was introduced for 'high-risk' neonates if maternal EBM was unavailable. Results: The pre-protocol and post-protocol had 34 and 38 infants respectively. There was a significant decrease between the pre-protocol and post-protocol mean days from CICU admission to EN initiation 8.28 days(±10.80) and 4.22(±3.92) respectively; p =0.04(0.55-8.68). Both groups showed decreased weight-for-age z-scores(WAZ) during admission. There was a significantly smaller drop in mean WAZ score in the post-protocol group -0.21(±0.42) compared to the pre-protocol group -0.59(±0.68); p =0.014(0.72-0.11). NEC incidence reduced from 14.7% to 7.89%, odds ratio 0.17 in the post-protocol group. Days from CICU admission to EN initiation, days on PN, CICU-LOS and hospital-LOS all decreased; although not statistically significant this may be attributable to a small sample size and could be clinically significant. Eight patients in the pre-protocol group didn't meet their nutritional requirements prior to discharge; this reduced to one patient in the post-protocol group. No patients developed NEC after moving from 'high-risk' to 'standard-risk'. Conclusion: The introduction of 'high-risk' and 'standard-risk' EN protocols improved EN delivery and growth whilst reducing NEC. A 'side-step' from 'high-risk' to 'standard-risk' appears safe in this small cohort.